Method for improving photoelectric conversion efficiency of perovskite solar cell based on acyl chloride material
By introducing acyl chloride additives into perovskite solar cells, the crystallization process of perovskite crystals is improved, and the problem of MACl residue affecting device stability is solved, and the effect of improving photoelectric conversion efficiency and reducing defect state density is achieved.
Patent Information
- Application Number
- CN202411898305.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The residual MACl in the subsequent annealing of perovskite solar cells affects the long-term working stability of the device, and it is difficult to completely remove existing additives, affecting device performance.
An acid chloride additive with C, S, and P as the center atoms is introduced to improve the crystallization process of perovskite crystals, improve the crystallization quality of the film, reduce the density of defect states, and thus improve the efficiency of solar cells.
By using acid chloride additives, the photoelectric conversion efficiency of perovskite solar cells is significantly improved, the defect state density of the film is reduced, and the non-radiative recombination loss is reduced.
Smart Images

Figure CN119730688A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of perovskite solar cells, and in particular to a method for improving the photoelectric conversion efficiency of perovskite solar cells based on acyl chloride materials. Background Art
[0002] With the rapid development of the global economy, energy demand has shown a trend of continuous growth. However, the limited reserves of fossil fuels and their serious damage to the environment make it difficult to support global energy demand in the long term, especially in the context of sustainable development. In order to meet this challenge, the development of clean and renewable alternative energy has become a top priority. This is not only a key way to solve the energy crisis, but also a necessary choice to reduce greenhouse gas emissions and protect the environment. As an abundant and clean renewable energy source, solar energy has broad development potential and can be converted into the required energy in a variety of ways. In recent years, new photovoltaic technologies represented by organic-inorganic halide lead-based perovskite solar cells (PSCs) have the ability to directly convert solar energy into electrical energy. Since their advent in 2009, they have quickly become a research hotspot in the photovoltaic field with their rapidly improving photoelectric conversion efficiency and low-cost preparation process, and are considered to be one of the most promising technologies. In addition, perovskite solar cells (PSCs) have attracted widespread attention and research worldwide due to their advantages such as high photoelectric conversion efficiency, low cost, and simple preparation process. In particular, in recent years, the photoelectric conversion efficiency in the laboratory has exceeded 26%, which is comparable to the performance of traditional silicon-based solar cells. Compared with traditional solar cells, the adjustable band gap and excellent light absorption ability of perovskite materials give them greater flexibility and application potential, especially in the field of flexible substrates and stacked cells. Perovskite materials have direct band gaps, high light absorption coefficients, long carrier diffusion lengths, and efficient charge transfer characteristics. It is these characteristics that enable perovskite solar cells to achieve extremely high photoelectric conversion efficiency in a short period of time. This rapidly developing photovoltaic technology has shown the potential to become an important solution for future clean energy.
[0003] However, the high efficiency of perovskite solar cells depends largely on the crystallization quality of perovskite films. Grain boundaries, defects and grain size during crystal growth have an important influence on carrier transport and recombination behavior. If the grains are too small or the grain boundaries are uneven, non-radiative recombination is easily induced, resulting in a shortened carrier lifetime, which in turn reduces the photoelectric conversion efficiency of the device. Therefore, improving the crystallization process of perovskite materials is the key to improving the performance of solar cells. In current research, attempts are made to use additive engineering to optimize the crystallization quality of perovskite films to improve device performance and stability. The mechanism is mainly to interact with the components or solvent molecules in the perovskite material to change the crystallization kinetics such as nucleation and growth, thereby achieving the purpose of depositing high-quality perovskite films on the substrate.
[0004] Some additives such as halide ions, metal ions and organic small molecules can optimize the crystallization process of perovskite. After adding a certain amount of MACl to the perovskite precursor, the researchers were able to significantly improve the crystallinity and film morphology of the perovskite crystals during the precipitation process from the precursor, greatly improving the absorption of light by the perovskite and the charge transfer performance of the film, and significantly improving the photoelectric conversion efficiency of the device. This solution has now become a widely used solution in the industry. Almost all high-efficiency devices reported have MACl involved in the deposition process of perovskite films (Nature volume 616, pages 724-730 (2023)). However, subsequent studies have found that MACl cannot be completely removed during the subsequent annealing process, and trace amounts of MACl will exist in the device, affecting the long-term working stability of the device. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. The present invention improves the crystallization process of perovskite crystals by introducing an acyl chloride additive with C, S, and P as the central atoms in the perovskite solar cell, improves the crystallization quality of the prepared perovskite film, and reduces the defect state density of the film, thereby improving the efficiency of the perovskite solar cell. On the one hand, the acyl chloride molecules can adjust the surface energy of the perovskite precursor solution, promote the uniform spreading of the perovskite precursor on the substrate, and facilitate the formation of a uniform and dense film; on the other hand, the Cl atoms in the acyl chloride molecules have high activity and can form a Cl-containing intermediate phase with the components in the perovskite precursor, thereby regulating the nucleation and growth process of the perovskite crystal, promoting the uniform growth of the grains, reducing the grain boundary defects, thereby forming large grains and high-quality perovskite films, and reducing the non-radiative recombination losses of the grain boundaries. Acyl chloride molecules generally have the characteristics of high saturated vapor pressure and low boiling point, are easy to remove after crystallization is completed, and can effectively reduce the influence of additive material devices. The use of acyl chloride additives can improve the crystallization process of perovskite solar cells and improve the photoelectric conversion efficiency of the prepared perovskite solar cells.
[0006] Specifically, the present invention provides the following technical solutions:
[0007] A first aspect of the present invention provides an acyl chloride material for a perovskite solar cell, wherein the acyl chloride material comprises at least one of a carbonyl chloride material, a sulfonyl chloride material and a phosphorus oxychloride material, wherein the carbonyl chloride material has a structure as shown in the following formula (1), the sulfonyl chloride material has a structure as shown in the following formula (2), and the phosphorus oxychloride material has a structure as shown in the following formula (3):
[0008]
[0009] R1, R2, R3, and R4 are each independently selected from H, halogen, substituted or unsubstituted C 1-6 Alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted cycloalkyl, substituted or unsubstituted phenyl, substituted or unsubstituted 5- to 6-membered heteroaryl.
[0010] According to an embodiment of the present invention, R1, R2, R3, and R4 are independently selected from H, halogen, substituted or unsubstituted C 1-6 Alkyl, substituted or unsubstituted C 2-6 Alkenyl, substituted or unsubstituted C 2-6 Alkynyl, substituted or unsubstituted C 3-8 cycloalkyl, substituted or unsubstituted phenyl, substituted or unsubstituted 5- to 6-membered heteroaryl.
[0011] According to an embodiment of the present invention, each of R1 to R4 is independently selected from H, F, Cl, Br, I, substituted or unsubstituted C 1-6 alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted phenyl, or 5- to 6-membered heteroaryl, wherein the C 1-6 The alkyl group, phenyl group, and 5- to 6-membered heteroaryl group may be independently substituted by one or more alkyl groups, halogenated alkyl groups, halogen groups, aryl groups, halogenated aryl groups, and amino groups.
[0012] According to an embodiment of the present invention, each of R1 to R4 is independently selected from H, F, Cl, substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted C 2-4 Alkenyl, substituted or unsubstituted C 2-4 alkynyl, substituted or unsubstituted phenyl, substituted or unsubstituted 5- to 6-membered heteroaryl, wherein the C 1-4 Alkyl, C 2-4 Alkenyl, C 2-4 Alkynyl, phenyl, and 5- to 6-membered heteroaryl may be independently substituted by one or more CH3, CH2CH3, CH2CH2CH3, F, Cl, Br, amino, phenyl, or benzyl.
[0013] According to an embodiment of the present invention, R1 to R4 are independently selected from CH3, CH2CH3, CH2CH2CH3, (CH2)3CH3, CH2CH(CH3)2, C(CH3)3, -CH 2( C6H5), -CH2CH2(C6H5), phenyl, pyridine, imidazole, pyrrole, furan or thiophene.
[0014] According to an embodiment of the present invention, the acyl chloride additive is selected from at least one of the following compounds:
[0015]
[0016]
[0017]
[0018] A second aspect of the present invention provides a perovskite solar cell, comprising a perovskite active layer, wherein the perovskite active layer comprises a perovskite material and the acyl chloride material mentioned in the first aspect.
[0019] According to an embodiment of the present invention, the molar ratio of the acyl chloride material to the perovskite material is (0.01-1): 1. According to a preferred embodiment, the molar ratio of the acyl chloride additive to the perovskite material is (0.01-0.5):1.
[0020] A third aspect of the present invention provides a perovskite solar cell, comprising:
[0021] Conductive substrate;
[0022] A dense layer, the dense layer is disposed on the conductive substrate;
[0023] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the dense layer;
[0024] A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer;
[0025] A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer;
[0026] and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the perovskite active layer is added with the acyl chloride material mentioned in the first aspect.
[0027] According to an embodiment of the present invention, the conductive substrate is selected from one or more of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass;
[0028] The material of the dense layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3;
[0029] The material of the mesoporous electron transport layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3;
[0030] The material of the mesoporous spacer layer is selected from one or more of ZrO2, SiO2, Al2O3, and BaTiO3;
[0031] The material of the porous counter electrode layer is carbon.
[0032] According to an embodiment of the present invention, the acyl chloride material is added to the perovskite precursor solution and is jointly filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer;
[0033] Alternatively, the acyl chloride material is filled into the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer before the perovskite precursor solution is filled, and then the perovskite precursor solution without the acyl chloride material is filled.
[0034] A fourth aspect of the present invention provides a method for improving the efficiency of a perovskite solar cell, comprising:
[0035] Filling a perovskite solution containing an acyl chloride material into the pore structure of a porous counter electrode layer, a mesoporous spacer layer, and a mesoporous electron transport layer of a perovskite solar cell to form a perovskite active layer;
[0036] Alternatively, the method includes filling the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer with an acyl chloride material before filling the perovskite precursor solution, and then filling the perovskite precursor solution without the acyl chloride material to form a perovskite active layer;
[0037] The acyl chloride material is the acyl chloride material described in the first aspect of the present invention.
[0038] The beneficial effects achieved by the present invention are at least:
[0039] The present invention improves the crystallization process of perovskite by introducing an acyl chloride material having -Cl and -M=O (M can be C, P, S, etc.) multifunctional groups into a perovskite solar cell, thereby improving the crystallization quality of the prepared perovskite film, reducing the defect state density of the film, and thus improving the efficiency of the perovskite solar cell. The acyl chloride molecules are used as additives. On the one hand, they can adjust the surface energy of the perovskite precursor solution, promote the uniform spreading of the perovskite precursor on the substrate, and facilitate the formation of a uniform and dense film; on the other hand, the Cl atoms in the acyl chloride molecules have electron-pulling properties, and the half of the side containing the O double bond has electron-pulling properties, so that Cl has high activity and can form a Cl-containing intermediate phase with the components in the perovskite precursor, thereby regulating the nucleation and growth process of the perovskite crystal, promoting the uniform growth of grains, reducing grain boundary defects, thereby forming a large grain and a high-quality perovskite film, and reducing the non-radiative recombination loss of the grain boundary. Acyl chloride molecules have the characteristics of high saturated vapor pressure and low boiling point. They are easy to remove after crystallization is completed, which can effectively reduce the impact of non-perovskite components on the device. Using acyl chloride materials as additives to prepare perovskite solar cells can improve the photoelectric conversion efficiency of perovskite solar cells. DETAILED DESCRIPTION
[0040] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0041] The present invention improves the crystallization process of perovskite by introducing an acyl chloride material with multifunctional groups into the perovskite solar cell, improves the crystallization quality of the prepared perovskite film, reduces the defect state density of the film, and thus improves the efficiency of the perovskite solar cell. On the one hand, the acyl chloride molecules can adjust the surface energy of the perovskite precursor solution, promote the uniform spreading of the perovskite precursor on the substrate, and facilitate the formation of a uniform and dense film; on the other hand, the Cl atom in the acyl chloride molecule has an electron-pulling property, and the half of the side containing the O double bond has an electron-donating property, so that Cl has a high activity and can form a Cl-containing intermediate phase with the components in the perovskite precursor, thereby regulating the nucleation and growth process of the perovskite crystal, promoting the uniform growth of the grains, reducing the grain boundary defects, thereby forming a large grain and a high-quality perovskite film, and reducing the non-radiative recombination loss of the grain boundary. The acyl chloride molecules have the characteristics of high saturated vapor pressure and low boiling point, are easy to remove after the crystallization is completed, can effectively reduce the influence of non-perovskite components on the device, and use acyl chloride additives to improve the crystallization process of perovskite solar cells Provide a new idea.
[0042] The acyl chloride material mentioned may be a carbonyl chloride material, a sulfonyl chloride material, or a phosphorus oxychloride material, and specifically has a structure shown in the following formula (1), formula (2) or formula (3):
[0043]
[0044] R1, R2, R3, and R4 are each independently selected from H, halogen, substituted or unsubstituted C 1-6 Alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted cycloalkyl, substituted or unsubstituted phenyl, substituted or unsubstituted 5- to 6-membered heteroaryl.
[0045] Among the materials of formula (1) to formula (3), only one of the materials can be selected to be added to prepare a perovskite solar cell, or two or more materials can be selected to be added simultaneously to prepare a perovskite solar cell. When two or more materials are selected to be added, they can be respectively from the structure shown in formula (1), or respectively from the structure shown in formula (2), or respectively from the structure shown in formula (3), or from any combination of the structures shown in formula (1) to formula (3). The specific selection can be made according to needs.
[0046] According to a specific embodiment, each of R1 to R4 is independently selected from H, F, Cl, Br, I, substituted or unsubstituted C 1-6 alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted phenyl, or 5- to 6-membered heteroaryl, wherein the C 1-6 The alkyl group, phenyl group, and 5- to 6-membered heteroaryl group may be independently substituted by one or more alkyl groups, halogenated alkyl groups, halogen groups, aryl groups, halogenated aryl groups, and amino groups.
[0047] According to a specific embodiment, each of R1 to R4 is independently selected from H, F, Cl, substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted C 2-4 Alkenyl, substituted or unsubstituted C 2-4 alkynyl, substituted or unsubstituted phenyl, substituted or unsubstituted 5- to 6-membered heteroaryl, wherein the C 1-4 Alkyl, C 2-4 Alkenyl, C 2-4 Alkynyl, phenyl, and 5- to 6-membered heteroaryl may be independently substituted by one or more CH3, CH2CH3, CH2CH2CH3, F, Cl, Br, amino, phenyl, or benzyl.
[0048] According to a specific embodiment, each of R1 to R4 is independently selected from CH3, CH2CH3, CH2CH2CH3, (CH2)3CH3, CH2CH(CH3)2, C(CH3)3, -CH 2( C6H5), -CH2CH2(C6H5), phenyl, pyridine, imidazole, pyrrole, furan or thiophene.
[0049] Herein, the substituents mentioned herein, when not specifically stated, include but are not limited to oxo (=O), fluorine, chlorine, bromine, iodine, hydroxyl, amino, carboxyl, alkyl, haloalkyl, hydroxyalkyl, aminoalkyl, aldehyde, aminoacyl, alkoxy, aminoalkyl, alkylthio, haloalkoxy, cyano, aryl, haloaryl, heteroaryl, alkenyl, alkynyl, heterocyclic radical, sulfhydryl, nitro, aryloxy, hydroxyalkoxy, benzyl, cyclopropyl, phenyl, or alkoxyalkyl, etc. According to a preferred embodiment, the substituents mentioned are alkyl, haloalkyl, halogen (fluorine, chlorine, bromine, iodine), aryl, and haloaryl. Each substituent can be used to adjust the electron cloud density on Cl and M=O to adjust the activity of Cl. According to a specific embodiment, the substituents mentioned are alkyl, haloalkyl, halogen, aryl, haloaryl, and amino.
[0050] Herein, the halogen mentioned can be specifically fluorine, chlorine, bromine, iodine, etc. Herein, "alkyl" includes 1-8 carbon atoms saturated straight or branched monovalent alkyl, wherein the alkyl can be independently optionally substituted by one or more substituents described in the present invention. According to some embodiments, the alkyl group contains 1-6 carbon atoms, and according to other embodiments, the alkyl group contains 1-4 carbon atoms. Further examples of alkyl groups include, but are not limited to, methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), n-butyl (-CH2CH2CH2CH3), 2-methylpropyl or isobutyl (-CH2CH(CH3)2), 1-methylpropyl or sec-butyl (-CH(CH3)CH2CH3), tert-butyl (-C(CH3)3) and the like. The alkyl group can be substituted by the substituents described in the present invention.
[0051] Alkenyl refers to a hydrocarbon group containing at least one carbon-carbon double bond. It can be a straight chain, branched chain or cyclic structure. According to some embodiments, the alkenyl group contains 2 to 10 carbon atoms, for example, 2 to 8 carbon atoms, 2 to 7 carbon atoms, 2 to 6 carbon atoms, 2 to 5 carbon atoms, 2 to 4 carbon atoms, etc.
[0052] Alkynyl refers to a hydrocarbon group containing at least one carbon-carbon triple bond. It can be a straight chain, branched chain or cyclic structure. According to some embodiments, the alkynyl group contains 2 to 10 carbon atoms, for example, 2 to 8 carbon atoms, 2 to 7 carbon atoms, 1 to 6 carbon atoms, 2 to 5 carbon atoms, 2 to 4 carbon atoms, etc.
[0053] The term "aryl" may be a monocyclic, bicyclic, and tricyclic carbon ring system, wherein at least one ring system is aromatic, wherein each ring system contains 3-7 atoms and has only one point of attachment to the rest of the molecule. The term "aryl" may be used interchangeably with the term "aromatic ring", such as aromatic rings may include phenyl, naphthyl and anthracene. Depending on the structure, an aryl group may be a monovalent group or a divalent group, i.e., an arylene group. An aryl group may be substituted with the substituents described herein.
[0054] The term "heteroaryl" refers to a monocyclic ring system in which one or more atoms of the heteroaryl ring are independently optionally substituted by heteroatoms (heteroatoms selected from N, O, P, S, where S or P is independently optionally substituted by one or more oxygen atoms to give groups such as SO, SO2, PO, PO2). The heteroaryl system can be attached to the main structure at any heteroatom or carbon atom to form a stable compound.
[0055] The present invention also provides a perovskite solar cell, comprising:
[0056] Conductive substrate;
[0057] A dense layer, the dense layer is disposed on the conductive substrate;
[0058] A mesoporous electron transport layer, wherein the mesoporous electron transport layer is located on the dense layer;
[0059] A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer;
[0060] A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer;
[0061] and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the above-mentioned acyl chloride material is added to the perovskite active layer.
[0062] Among them, the conductive substrate can choose a variety of materials, such as FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, PEN / ITO conductive glass. For example, indium tin oxide (ITO) or fluorine-doped tin oxide (FTO) glass can be used as the substrate of the battery to provide good optical transparency and conductivity. The dense layer is located on the conductive substrate layer, and the commonly used dense layer materials include but are not limited to TiO2, SnO2, ZnO, BaSnO3, SrTiO3, etc. Commonly used mesoporous electron transport layer materials include TiO2, SnO2, ZnO, BaSnO3, SrTiO3, etc. These materials are used to efficiently transfer electrons to the electrode and prevent holes from being transmitted to the cathode. The materials that can be used as mesoporous spacer layers are usually some inorganic oxide materials (such as TiO2, ZrO2, Al2O3). These materials play a role of isolation and protection in perovskite solar cells, and also help to improve the performance of the battery. For example, SiO2 and ZrO2 are often used as spacer layer materials. The spacer layer film prepared by SiO2@ZrO2 nanoparticles has the characteristics of ultra-flatness and crack-free, which can effectively improve the power conversion efficiency of perovskite solar cells. In addition, Al2O3 is also widely used in spacer layer materials, especially when used in combination with ZrO2, which can significantly improve the photoelectric conversion efficiency. According to a specific embodiment, the mesoporous spacer layer material includes but is not limited to ZrO2, SiO2, Al2O3, BaTiO3. The material of the porous counter electrode layer is a carbon material.
[0063] The perovskite active layer is filled in the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer. The perovskite active layer includes a perovskite material and the mentioned acyl chloride additive. The mentioned perovskite material is usually composed of an organic-inorganic hybrid perovskite material with an ABX3 structure, such as methylamine lead iodine (CH3NH3PbI3), methylamine lead bromide (MAPbBr3), formamidine lead iodine (FAPbI3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3) and mixed cations, anions and perovskite materials and the like. The perovskite material and the acyl chloride additive can be added dropwise to the mesoporous structure, left to stand for a period of time, and annealed on a hot stage at 50-80°C for 5-50 hours (according to a preferred embodiment, annealing can be performed at a temperature of 65°C for 15 hours).
[0064] The perovskite solar cell mentioned above can be obtained by a common preparation method in the art. According to a specific embodiment, the acyl chloride additive is added to the perovskite precursor solution and is filled in the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer.
[0065] According to a specific embodiment, the acyl chloride material can also be filled into the pore structure of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer before filling the perovskite precursor solution, and then the perovskite precursor solution without acyl chloride material is filled to form a perovskite active layer.
[0066] Compared with the case where no material mentioned in the present invention is added, the addition of acyl chloride materials can increase the photoelectric conversion efficiency of perovskite solar cells by up to 10% to 20%, for example, about 13% to 18%.
[0067] The technical solution of the present invention is described below by specific examples. It should be noted that these examples are only used to facilitate the understanding of those skilled in the art and should not be regarded as limiting the scope of protection of the present invention. The substances listed in the table of the present invention are used as materials to prepare perovskite solar cells, which have been verified to significantly improve the photoelectric conversion efficiency of perovskite solar cells. Unless otherwise specified, the reagents used in the examples can be obtained commercially, or can be prepared in combination with the common knowledge of those skilled in the art.
[0068] Example 1
[0069] Example 1 Taking propionyl chloride as an example, a perovskite solar cell was prepared, comprising:
[0070] (1) The processing of glass substrate mainly includes three steps: cutting / laser etching and cleaning.
[0071] Cutting: Use a glass cutter to cut the original glass into the required size. Before cutting, make sure the glass surface is clean to avoid defects during the cutting process. After cutting, grind the glass to smooth the sharp edges.
[0072] Laser etching: Use laser etching equipment to adjust the laser power and parameters to control the etching depth and accuracy, and perform high-precision processing on the glass substrate. Laser etching can remove part of the material to form the desired pattern or structure.
[0073] Cleaning: After cutting and laser etching, the glass substrate is cleaned in an ultrasonic cleaner using deionized water and detergent for multiple rounds to remove residual impurities and contaminants. After cleaning, it is spun or dried to ensure that there is no residual moisture on the surface.
[0074] (2) Preparation of dense layer and printing and sintering of three-layer membrane.
[0075] The diisopropyl di(acetylacetonate)titanate solution is atomized and then sprayed on the FTO surface of the above-mentioned glass, decomposed at high temperature (450°C) to obtain a dense TiO2 dense layer, and then cooled naturally; then a titanium dioxide electron transport layer, a zirconium dioxide spacer layer, and a carbon counter electrode layer are deposited on the glass sprayed with the dense layer by printing layer by layer, and sintered at different temperatures to ensure the stability and performance of each layer.
[0076] Specifically, a nano-titanium dioxide electron transport layer is deposited on the dense TiO2 layer using screen printing technology, and the pore-forming agent is removed to form a mesoporous titanium dioxide film.
[0077] A zirconium dioxide layer is formed on the mesoporous titanium dioxide film by using a screen printing technique, and then dried at 70° C. to remove the solvent, thereby forming a zirconium dioxide film.
[0078] Finally, a carbon counter electrode layer is deposited on the zirconium dioxide film, usually by screen printing or doctor blade technology, and sintered at an appropriate temperature to ensure its stability.
[0079] (3) Prepare perovskite solution.
[0080] The experiment was divided into a control group and an experimental group.
[0081] The control group was prepared by weighing 4.61 g (10 mmol) of lead iodide, 0.398 g (2.5 mmol) of iodomethylamine, and 0.10 g (1.5 mmol) of chloromethylamine, and dissolving them in a mixed solvent of 6400 μL of N-N-dimethylformamide (DMF) and 1600 μL of dimethyl sulfoxide (DMSO). The obtained solution was the perovskite precursor solution of the control group.
[0082] The experimental group was prepared by adding propionyl chloride (0.1 mmol) into the perovskite precursor solution of the control group.
[0083] Then, the precursor solutions of the control group and the experimental group were stirred at 50° C. for 2 h to obtain the perovskite solution of the control group and the perovskite solution of the experimental group.
[0084] (4) Filling of perovskite solution and crystal growth. First, cover the non-filled area with tape, then use a pipette to transfer the prepared perovskite solution of the experimental group and the control group and drop it on the surface of the carbon film (filling amount is 270-280 μL). After standing for a certain period of time, place it on a hot plate at 65°C for annealing for 15 hours. After the solvent is completely removed, the battery preparation process is completed, and the experimental group battery and the control group battery are obtained respectively.
[0085] PCE performance tests were performed on the prepared experimental group batteries and control group batteries.
[0086] The PCE test of solar cells is carried out by combining a solar simulator and a digital source meter efficiency test system to obtain the JV curve of the test device. Before the test, a standard silicon cell must be used as a reference and the calibrated light intensity must be 1 standard sunlight (AM1.5 G, 100mW / cm 2 ). The scanning range is 16.0V~-1.0V, and the scanning step is 0.2V. PCE (photovoltaic conversion efficiency) refers to the efficiency of solar cells converting received light energy into electrical energy, and is a key indicator for measuring battery performance. PCE is jointly determined by VOC, JSC and FF. Among them, VOC (open circuit voltage) refers to the voltage difference between the two ends of the solar cell when there is no load, which can reflect the internal potential energy of the battery and is usually related to the band gap and charge transfer characteristics of the material. JSC (short circuit current density) refers to the maximum current density that can be generated under short circuit conditions (that is, when there is no voltage at both ends of the battery), which reflects the material's ability to absorb light and the carrier transfer efficiency. FF (fill factor) refers to the ratio of the maximum power point voltage (VMP) to the product of the open circuit voltage (VOC) and the maximum power point current (JMP), which reflects the electrical performance and internal loss of the battery.
[0087] The battery performance of the control group and the experimental group is shown in Table 1 below:
[0088] Table 1 Performance characterization results
[0089]
[0090] It can be seen from the results given in Table 1 that the photoelectric conversion efficiency of the perovskite solar cell prepared by the present invention is improved compared with the control group due to the addition of propionyl chloride.
[0091] Example 2
[0092] Example 2 Taking 2-phenylacetyl chloride as an example, a perovskite solar cell was prepared.
[0093] The preparation process is similar to that of Example 1. The difference is that in step (3) of Example 2, a perovskite solution with different components is used.
[0094] The control group was prepared by weighing 4.61 g (10 mmol) of lead iodide, 0.1 g (0.625 mmol) of iodomethylamine, 0.323 g (1.875 mmol) of iodoformamidine, and 0.10 g (1.5 mmol) of chloromethylamine and dissolving them in a mixed solvent of 6400 μL of N-N-dimethylformamide (DMF) and 1600 μL of dimethyl sulfoxide (DMSO). The obtained perovskite precursor solution was obtained in the control group.
[0095] The experimental group was as follows: 2-phenylacetyl chloride (0.1 mmol) was additionally introduced into the perovskite precursor solution of the control group.
[0096] The performance of the perovskite solar cells prepared by the control group and the experimental group are shown in Table 2:
[0097] Table 2 Performance characterization results
[0098]
[0099] It can be seen from the results given in Table 2 that the photoelectric conversion efficiency of the perovskite solar cell prepared by the present invention is improved compared with the control group.
[0100] Example 3
[0101] The preparation process of Example 3 is similar to the above process, except that the control group of Example 3 introduces chloromethylamine hydrochloride as an additive into the perovskite solution of the control group in Example 1. The experimental group introduces formyl chloride into the perovskite solution of the control group in Example 1.
[0102] Control group: 4.61 g (10 mmol) of lead iodide, 0.398 g (2.5 mmol) of iodomethylamine, 0.10 g (1.5 mmol) of chloromethylamine, and chloromethylamine hydrochloride (1.5 mmol) were dissolved in a mixed solvent of 6400 μL of N-N-dimethylformamide (DMF) and 1600 μL of dimethyl sulfoxide (DMSO), and the obtained perovskite precursor solution was obtained in the control group;
[0103] The experimental group was as follows: 4.61 g (10 mmol) of lead iodide, 0.398 g (2.5 mmol) of iodomethylamine, 0.10 g (1.5 mmol) of chloromethylamine, and formyl chloride (0.1 mmol) were dissolved in a mixed solvent of 6400 μL of N-N-dimethylformamide (DMF) and 1600 μL of dimethyl sulfoxide (DMSO).
[0104] The performance of the perovskite solar cells prepared by the control group and the experimental group are shown in Table 3 below:
[0105] Table 3 Performance characterization results
[0106]
[0107] The results show that compared with the performance of perovskite solar cells with ordinary chlorine additives, the photoelectric conversion efficiency of the perovskite solar cells prepared by the present invention is improved.
[0108] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. An acyl chloride material for perovskite solar cells, characterized in that: The acyl chloride material includes at least one of a phosgene material, a sulfonyl chloride material and a phosphorus oxychloride material. The phosgene material has a structure as shown in the following formula (1), the sulfonyl chloride material has a structure as shown in the following formula (2), and the phosphorus oxychloride material has a structure as shown in the following formula (3): R1 to R4 are each independently selected from H, halogen, substituted or unsubstituted C 1-6 Alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted cycloalkyl, substituted or unsubstituted phenyl, substituted or unsubstituted 5- to 6-membered heteroaryl.
2. The acyl chloride material for perovskite solar cells according to claim 1, characterized in that: The R1-R4 are independently selected from H, F, Cl, Br, I, substituted or unsubstituted C 1-6 alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted phenyl, or 5- to 6-membered heteroaryl, wherein the C 1-6 The alkyl group, phenyl group, and 5- to 6-membered heteroaryl group may be independently substituted by one or more alkyl groups, halogenated alkyl groups, halogen groups, aryl groups, halogenated aryl groups, and amino groups.
3. The acyl chloride material for perovskite solar cells according to claim 1, characterized in that: The R1 to R4 are independently selected from H, F, Cl, substituted or unsubstituted C 1-4 Alkyl, substituted or unsubstituted C 2-4 Alkenyl, substituted or unsubstituted C 2-4 alkynyl, substituted or unsubstituted phenyl, substituted or unsubstituted 5- to 6-membered heteroaryl, wherein the C 1-4 Alkyl, C 2-4 Alkenyl, C 2-4 Alkynyl, phenyl, and 5- to 6-membered heteroaryl may be independently substituted by one or more CH3, CH2CH3, CH2CH2CH3, F, Cl, Br, amino, phenyl, or benzyl.
4. The acyl chloride material for perovskite solar cells according to claim 1, characterized in that: The R1 to R4 are independently selected from CH3, CH2CH3, CH2CH2CH3, (CH2)3CH3, CH2CH(CH3)2, C(CH3)3, -CH 2( C6H5), -CH2CH2(C6H5), phenyl, pyridine, imidazole, pyrrole, furan or thiophene.
5. The acyl chloride material for perovskite solar cells according to claim 1, characterized in that: The acyl chloride material is selected from at least one of the following compounds:
6. A perovskite solar cell, characterized in that: Comprising a perovskite active layer, the perovskite active layer comprising a perovskite material and an acyl chloride material for a perovskite solar cell according to any one of claims 1 to 5; Optionally, the molar ratio of the acyl chloride material to the perovskite material is (0.01-1):
1.
7. A perovskite solar cell, characterized in that: include: Conductive substrate; A dense layer, the dense layer is disposed on the conductive substrate; A mesoporous electron transport layer, wherein the mesoporous electron transport layer is disposed on the dense layer; A mesoporous spacer layer, wherein the mesoporous spacer layer is disposed on the mesoporous electron transport layer; A porous counter electrode layer, wherein the porous counter electrode layer is disposed on the mesoporous spacer layer; and a perovskite active layer, wherein the perovskite active layer is filled in the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer, and the perovskite active layer is added with the acyl chloride material for a perovskite solar cell according to any one of claims 1 to 5.
8. The perovskite solar cell according to claim 7, characterized in that: The conductive substrate is selected from one or more of FTO conductive glass, ITO conductive glass, PET / ITO conductive glass, and PEN / ITO conductive glass; The material of the dense layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; The material of the mesoporous electron transport layer is selected from one or more of TiO2, SnO2, ZnO, BaSnO3, and SrTiO3; The material of the mesoporous spacer layer is selected from one or more of ZrO2, SiO2, Al2O3, and BaTiO3; The material of the porous counter electrode layer is carbon.
9. The perovskite solar cell according to claim 7, characterized in that: The acyl chloride material is added to the perovskite precursor solution and is filled into the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer to obtain the perovskite active layer; Alternatively, the acyl chloride material is filled into the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer before the perovskite precursor solution is filled, and then the perovskite precursor solution without the acyl chloride material is filled.
10. A method for improving the efficiency of a perovskite solar cell, characterized in that: The method comprises filling a perovskite solution containing an acyl chloride material into the pore structure of a porous counter electrode layer, a mesoporous spacer layer and a mesoporous electron transport layer of a perovskite solar cell to form a perovskite active layer; Alternatively, the method includes filling the pore structures of the porous counter electrode layer, the mesoporous spacer layer and the mesoporous electron transport layer with an acyl chloride material before filling the perovskite precursor solution, and then filling the perovskite precursor solution without the acyl chloride material to form a perovskite active layer; The acyl chloride material is the acyl chloride material for perovskite solar cells according to any one of claims 1 to 5.